Glycopeptide-mimetic carbon dots/graphene oxide mediated fluorescent-recovery sensor for detecting Salmonella typhimurium - Wang, Xuan; Lin, Zhenhao; Cai, Jihai; Wang, Xiaoying (Talanta (Oxford), 2025)
Food safety issues associated with Salmonella present serious health risks, making detection crucial for public health protection. This study develops an efficient strategy for the capture of Salmonella typhimurium (S. typhimurium) based on the affinity between glycopeptide-mimetic carbon dots (g-CDs) and the type I fimbriae of S. typhimurium. The g-CDs were obtained by carbonizing mannose and histidine, which can be stored without light protection for over 90 days. Specially, the incorporation of histidine reduced the dissociation constant of g-CDs with lectin ConA from 135 μM to 25.4 μM. Further, g-CDs were anchored to phenylboronic acid-functionalized graphene oxide (GO-PBA) via dynamic borate bonds to create a fluorescent turn-on probe (CDs/GO-PBA). This probe exhibited a liner range of 104–107 CFU mL−1, achieving 2370 CFU mL−1 detection limit with a recovery rate ranging from 93 % to 103 % in chicken. The fluorescent sensor provides a promising strategy for the detection of S. typhimurium in food. [Display omitted] •g-CDs were prepared by hydrothermal reaction of mannose and histidine.•Affinity of g-CDs with FimH was enhanced by multivalent presentation of residues.•Fluorescent recovery was based on S. typhimurium induced broken of borate bond.•S. typhimurium was detected within 104–107 CFU mL−1 with LOD of 2370 CFU mL−1.•Recovery S. typhimurium in chicken was 93–103 % with RSD less than 2 %.